Analisis Penerapan Blended Learning terhadap Motivasi dan Hasil Belajar Siswa Kelas V di UPTD SD Negeri Oli′O - Wiwin Maryani Mada; Winardi Budi Setiawan; Ahmad Husin (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
This study aims to analyze the implementation of blended learning on the motivation and learning outcomes of fifth-grade students at UPTD SD Negeri Oli′O. This study employs a quantitative approach with a quasi-experimental design. The research subjects were fifth-grade students, comprising an experimental class using LMS-based blended learning and a control class using conventional learning. Data were collected through learning motivation questionnaires and learning outcome tests administered before and after the intervention. Data analysis was conducted using the Kolmogorov-Smirnov normality test, Levene’s homogeneity test, F-test ANOVA, and paired samples t-test. The results indicate that the implementation of the blended learning model has a positive effect on students’ motivation and learning outcomes. Students who participated in blended learning demonstrated better learning motivation compared to those in the conventional learning group. Additionally, student learning outcomes improved because learning materials could be flexibly accessed again via online platforms, thereby providing students with broader opportunities to understand the material independently.